Improved Understanding of IUD and Implant Family Planning Acceptors in Family Planning Services at Solo Peduli Clinic - Uki Retno Budihastuti; Abdurahman Laqif; Eriana Melinawati; Teguh Prakosa; Hermawan Udiyanto; Heru Priyanto; Darto Darto; Affi Angelia Ratnasari; Asih Anggraeni; Dympna Prameilita Prisasanti (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Family planning acceptor's understanding of intra uterine device (IUD) and implant contracep